Breakfast Intake and Learning Concentration - Taufiqurrahman Taufiqurrahman; Viska Karera (Humanistic Network for Science and Technology (HNST), 2017)
The concentration of learning is the ability to focus the mind on learning activities that can be influenced by breakfast intake as well as hydration status. Based on preliminary study on 10 students, it was found that there were 7 students who did not have breakfast and 8 students chose to consume energy drinks and mixed drinks instead of consuming water when thirst which caused the body to dehydrate. This study aims to analyze the relationship between breakfast intake and hydration status with learning concentration of students in elementary school Pacar Keling 6 Surabaya city, in February 2017 with cross sectional design. The subjects of the study were students of class III, IV and V chosen by random. The result of the analysis using Chi square test showed that there was a correlation between the intake of breakfast with the study concentration (p-value = 0,048) and there was no correlation between the hydration status and the study concentration (p-value = 0,307). It can be concluded that students with poor breakfast intake have low learning concentrations, the effects caused by mild dehydration conditions only in mood (mood) not on concentration and hydration status can be determined by the type of food and beverages consumed. Keywords: Breakfast, Learning concentration, Students, Elementary school